Diurnal raptors of West Africa woodland-farmland mosaics: Data from walking-transects in eastern Guinea-Bissau. Issue 1 (May 2020) - Rodrigues, Patrícia; Mirinha, Marco; Palma, Luís
Guinea-Bissau is a small country in West Africa, which in spite of its rich biodiversity and the high proportion of protected areas remains under-surveyed in relation to most animal groups, including raptors. The first scientific articles about raptors were only very recently issued. Here, we report raptor occurrence data from eastern Guinea-Bissau. Raptors were surveyed in the dry season along transects walked around 21 villages in a rural woodland-farmland mosaic landscape. The raptor assemblage is composed of 25 species of which the hooded vulture, the lizard buzzard and the African harrier-hawk were the species more often encountered, followed by the African white-backed vulture. The palm-nut vulture, black kite, brown snake-eagle, grasshopper buzzard, African hawk-eagle, grey kestrel and lanner falcon were secondary, although not uncommon species. The remaining species were seldom recorded. The study complements previous knowledge on this bird group, specifically in the central-eastern part of the country, and reaffirms the international relevance of Guinea-Bissau for the conservation of the hooded and African white-backed vultures.